66.2k views
2 votes
Simplify the equation -x^3 + 5x + 7x^2 +8x^3 - (-x^3 +x)​

User Chromigo
by
5.2k points

2 Answers

4 votes

Let's simplify step-by-step.

−x^3 + 5x + 7x^2 + 8x^3 − ( −x^3 + x )

Distribute the Negative Sign:

= −x^3 + 5x + 7x^2 + 8x^3 + −1 ( −x^3 + x )

= −x^3 + 5x + 7x^2 + 8x^3 + −1 ( −x^3 ) + −1x

= −x^3 + 5x + 7x^2 + 8x^3 + x^3 + −x

Combine Like Terms:

= −x^3 + 5x + 7x^2 + 8x^3 + x^3 + −x

= ( −x^3 + 8x^3 + x^3 ) + ( 7x^2 ) + ( 5x + −x )

= 8x^3 + 7x^2 + 4x

Answer:

= 8x^3 + 7x^2 + 4x

User Mohebifar
by
5.4k points
5 votes

Answer:

8x³ + 6x² + 5x

Explanation:

User Cartman
by
5.2k points